2003
DOI: 10.1001/archinte.163.21.2594
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fatal and Nonfatal Lactic Acidosis With Metformin Use in Type 2 Diabetes Mellitus

Abstract: There is no evidence to date that metformin therapy is associated with an increased risk of lactic acidosis or with increased levels of lactate compared with other antihyperglycemic treatments if the drugs are prescribed under study conditions, taking into account contraindications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(53 citation statements)
references
References 156 publications
1
50
0
2
Order By: Relevance
“…Systematic reviews and case series have shown a low incidence of metformin-associated lactic acidosis [8,9]. Salpeter et al [10] conducted a comparative review and found that lactic acidosis was present in 4.3 cases per 100,000 patient-years among metformin users and in 5.4 cases among non-metformin users. …”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and case series have shown a low incidence of metformin-associated lactic acidosis [8,9]. Salpeter et al [10] conducted a comparative review and found that lactic acidosis was present in 4.3 cases per 100,000 patient-years among metformin users and in 5.4 cases among non-metformin users. …”
Section: Introductionmentioning
confidence: 99%
“…The true incidence of metformin-associated lactic acidosis (MALA) remains unknown. 13 The average rate is estimated to be 0.03 cases per 1000 patient-years, with 50% of cases being fatal. 14 However, evidence linking elevated lactic acid levels to metformin use or metformin levels is poor.…”
mentioning
confidence: 99%
“…15) To clarify the mechanism of this side effect, we have attempted to find genes whose expression changed by treatment with buformin through the screening of the subtraction cDNA library constructed by the suppression subtractive hybridization method. 9) We found that buformin suppressed expression of the GAPD gene in HepG2 cells and the suppression was dependent on the period of exposure.…”
Section: Discussionmentioning
confidence: 99%